Sosialisasi pada Masyarakat Tentang Dampak Radiasi Tower Bts Operator Seluler pada Masyarakat di Kelurahan Aie Pacah Kecamatan Koto Tangah Kota Padang - Baharuddin, Baharuddin; Fernandez, Rudy; Andre, Hanalde; Zurnawita; Firdaus (Jurnal Andalas: Rekayasa dan Penerapan Teknologi, 2024)
This article discusses the results of community outreach activities related to the impact of radiation from cellular operator BTS towers in Aie Pacah Village, Koto Tangah District, Padang City. This outreach aims to improve public understanding of the potential health impacts of electromagnetic radiation emitted by BTS towers and provide accurate information based on scientific studies, especially amidst concerns from the local community. This activity involved lecturers and doctoral students from the field of telecommunications engineering, and presented expert speakers. The method of implementing the outreach included interactive delivery of materials, discussions, and question and answer sessions to capture public concerns and provide science-based solutions. Evaluation was conducted using pre- and post-outreach surveys to measure improvements in public understanding. The results of the activity showed that 78% of participants initially had high concerns about the health impacts of BTS tower radiation. However, after the outreach, 85% of participants reported a better understanding of risk mitigation and benefits of telecommunications infrastructure, and felt more confident in the safety of radiation exposure according to international standards. This outreach is expected to have a positive impact on improving public literacy about communication technology and health, as well as encouraging cooperation between the community, government, and telecommunications operators to continue to provide transparent information. As a follow-up, similar activities are planned to reach other areas with different social characteristics.